2020
DOI: 10.1158/1055-9965.epi-20-0074
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in Cancer Biomarker Discovery and Validation with Emphasis on Circulating Tumor DNA

Abstract: Despite significant investment of funds and resources, few new cancer biomarkers have been introduced to the clinic in the last few decades. Even though many candidates produce promising results in the laboratory, deficiencies in sensitivity, specificity and predictive value make them less than desirable in a patient setting. This review will analyze these challenges in detail as well as discuss false discovery, problems with reproducibility and tumor heterogeneity. Circulating tumor DNA (ctDNA), an emerging c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…The main obstacles in the proteomic study of patient samples with any disease are the patient physiology (co-morbidities, co-infections, pregnancies), sample preparation, and protein separation and identification methods [96,97]. Several studies have shown that different separation and identification methods are associated with significant differences in the proteins identified in the same type of sample (same type of biological sample and disease stage) and disease [48,98,99].…”
Section: Proteomics and Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The main obstacles in the proteomic study of patient samples with any disease are the patient physiology (co-morbidities, co-infections, pregnancies), sample preparation, and protein separation and identification methods [96,97]. Several studies have shown that different separation and identification methods are associated with significant differences in the proteins identified in the same type of sample (same type of biological sample and disease stage) and disease [48,98,99].…”
Section: Proteomics and Cervical Cancermentioning
confidence: 99%
“…One of the main problems in the study of biomarkers is the limited number of available samples, which increases the chance of false-positive candidates [99,100]. In CC, the type of biological samples that are most useful for finding biomarkers are tumor tissue, cervical, vaginal fluid, blood, and even saliva.…”
Section: Proteomics and Cervical Cancermentioning
confidence: 99%
“…One root cause for this challenge arises from the use, in early development, of a cohort that is defined by a certain genetic or environmental background (in order to have sufficient disease homogeny to develop and assess a molecular biomarker) thus introducing a sample bias [48] , [50] , [53] . Such bias becomes an issue when validating predictive tools developed in a well-defined study population and compounded when translating such biomarkers into clinical practice – where every individual patient poses unique challenges to the biomarker: tumor location and heterogeneity, co-morbidities, lifestyle and environmental influences, as well as an individual clinical care team with local limitations or care choices [54] , [65] .…”
Section: Translational Research and Clinical Adoptionmentioning
confidence: 99%
“…60 Obtaining cervical material may be important as tumors >1 cm in diameter may be required to raise blood levels of ct DNA. 61 Shed tumor cells and cell-free DNA can pass through the fallopian tube and uterine cavity to the cervical os, without the significant dilution that occurs when DNA is shed from the cancer into peripheral blood. Recent development of a repetitive element aneuploidy sequencing system (RealSeq) to detect aneuploidy in ctDNA from as little as 3 pg of DNA in relatively small amounts of plasma promises to improve sensitivity for early stage high grade ovarian cancers with copy number abnormalities.…”
Section: Improving the Initial Stage Of Screeningmentioning
confidence: 99%